Biochemical parameters and markers of preclinical pathology of carotid artery wall in patients with different levels of cardiovascular risk by the ESH/ESC scale (2003, 2007) - S. Zh. Urazalina; A. N. Rogoza; T. V. Balakhonova; Yu. A. Karpov; V. V. Kukharchuk; S. A. Boytsov (Кардиоваскулярная терапия и профилактика, 1970)
Aim. To study the levels of biochemical markers of cardiovascular risk (CVR) and the ultrasound-assessed target organ damage (TOD), such as intima-media thickness (IMT), atherosclerotic plaques (AP) in carotid arteries (CA), and left ventricular myocardial mass index (LVMMI), in patients with low and intermediate risk by the SCORE scale (ESH/ ESC 2003, 2007). Material. The study included 600 individuals aged 30-65 years (445 women, 155 men) with low and intermediate CVR by SCORE scale, without manifested atherosclerotic pathology or diabetes mellitus. Methods. CVR was stratified by: SCORE scale and clinical recommendations by ESH/ESC (2003, 2007); duplex CA ultrasound, IMT and CA AP assessment; Doppler echocardiography with LVMMI calculation (Penn-cube method); blood biochemistry with lipid profile, blood glucose, and serum creatinine (Cr) level assessment. Results. Dyslipidaemia was observed in all clinical groups; however, no significant differences between the groups were observed for the participants aged ≤45 years. In participants aged 45-55 and ≥55 years, there was a statistically significant IMT difference between low and intermediate risk groups (р=0,03 and 0,01, respectively). Conclusion. The proportion of people with dyslipidaemia was high in all risk groups, regardless of age. CA AP were registered across all groups, regardless of risk level and age. No statistically significant differences were observed for the groups “intermediate risk, one AP” and “high risk, 1 AP”.